Rancang Bangun Sistem Informasi Retensi Rekam Medis dengan Metode Imaging Berbasis Web - Ahmad Junaidi; Khairul Zaman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Medical record is a file that contains notes and documents about the patient's identity, examination, treatment, actions and other services that have been given to the patient. Based on Minister of Health Regulation No.269 / Menkes / Per / III / 2008 the medical record file can be destroyed (retention) after being stored for a period of 5 (five) years from the last date the patient was treated or returned to avoid the buildup of non-active medical record documents. As one of the private hospitals in the city of Padang that has been operational for 14 years, Siti Rahmah Islamic Hospital has carried out the process of destroying medical record documents with imaging methods and storing them to an external hard drive before the medical record file is destroyed to anticipate various needs. relating to medical records, for example, a medical record that is still valuable to be needed can be searched and reprinted. However, the method used is not optimal because of the potential for data loss and the difficulty of the data search process and has not been managed using an information system in the form of a truly computerized program. Optimizing data processing is needed so that integrity, access rights and data availability can be maintained. The application system that will be proposed later uses PHP and Mariadb programming and web-based. The results of the image will be processed in an application and stored in the database. The diverse data will be managed well, easily and safely in a well-structured system. Keywords: Information Systems, Retention, Imaging, Medical Records, Web